2015
DOI: 10.7150/ijbs.10174
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Protects Astrocytes from ROS-Induced Damage through Inhibition of Mitochondria-Mediated Cell Death Pathway

Abstract: Coenzyme Q10 (CoQ10) acts by scavenging reactive oxygen species to protect neuronal cells against oxidative stress in neurodegenerative diseases. The present study was designed to examine whether CoQ10 was capable of protecting astrocytes from reactive oxygen species (ROS) mediated damage. For this purpose, ultraviolet B (UVB) irradiation was used as a tool to induce ROS stress to cultured astrocytes. The cells were treated with 10 and 25 μg/ml of CoQ10 for 3 or 24 h prior to the cells being exposed to UVB irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 22 publications
2
48
0
1
Order By: Relevance
“…The target of this antioxidant is the inner mitochondrial membrane (Zaki 2016), making ubiquinol an antioxidant that could potentially ameliorate secondary injury after a TBI. Specifically, ubiquinol decreases the production of ROS, which prevents mitochondrial dysfunction by stabilizing the membranes and improving energy production and biogenesis, as well as inhibiting cell death via pathways in the mitochondria (Jing et al 2015). As an antioxidant that targets the inner mitochondrial membrane, ubiquinol could be a supplemental treatment to decrease the severity of secondary injury after TBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The target of this antioxidant is the inner mitochondrial membrane (Zaki 2016), making ubiquinol an antioxidant that could potentially ameliorate secondary injury after a TBI. Specifically, ubiquinol decreases the production of ROS, which prevents mitochondrial dysfunction by stabilizing the membranes and improving energy production and biogenesis, as well as inhibiting cell death via pathways in the mitochondria (Jing et al 2015). As an antioxidant that targets the inner mitochondrial membrane, ubiquinol could be a supplemental treatment to decrease the severity of secondary injury after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…These antioxidants combat oxidative stress by ameliorating the overproduction of ROS and preventing mitochondrial DNA damage (Schmelzer & Doring 2012). Another important antioxidant that occurs naturally in the body is ubiquinol, the reduced form of CoQ10, which can protect neuronal cells from oxidative stress (Jing et al 2015). After age 40, mitochondrial capacity to reduce ubiquinone to ubiquinol progressively declines (Olivieri et al 2013).…”
Section: Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that the apoptotic pathway is the most important mechanism involved in the process of killing malignant cells with anticarcinogens (32,33). Several studies have also shown that OSW-1 can induce calcium-or caspase-8-dependent cleavage of Bcl-2-mediated apoptosis (34,35).…”
Section: Apoptosis Is the Main Cause Of Lovo Cell Death After Exposurmentioning
confidence: 99%
“…PARP inhibitors became valuable tools in treating cancer cells harboring DNA repair defect with the combination of either radio-or chemotherapy [39][40][41]. In addition to several orally-administered PARP inhibitors that are under active clinical development, recently ABT-888 (veliparib) has emerged as an effective drug in treating various solid tumors [42] partially via modulating mitochondrial activity [43,44].Although UV radiation has been shown to trigger morphological [45,46] and functional changes of mitochondria [47][48][49], published data led to contradictory results most likely due to the diversity of applied UV spectrum, UV dose, and cell type. Studies using UVC irradiation revealed that UVC induced mitochondrial hyperfusion and resulted in enhanced ATP synthesis via oxidative phosphorylation (OXPHOS) [50].…”
mentioning
confidence: 99%